2011
DOI: 10.2136/vzj2009.0186
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Precipitation Spatial Resolution on the Hydrological Response of an Integrated Distributed Water Resources Model

Abstract: Precipita on is a key input variable to hydrological models, and the spa al variability of the input is expected to impact the hydrological response predicted by a distributed model. In this study, the eff ect of spa al resolu on of precipita on on runoff , recharge and groundwater head was analyzed in the Alergaarde catchment in Denmark. Six diff erent precipita on spa al resolu ons were used as inputs to a physically based, distributed hydrological model, the MIKE SHE model. The results showed that the resol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
44
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 47 publications
(46 citation statements)
references
References 26 publications
2
44
0
Order By: Relevance
“…These authors used rainfall datasets at spatial resolutions of 0.05 • , 0.1 • , 0.25 • and 0.5 • . Results from this study also corroborate the findings of Fu et al [37], where the authors demonstrated that, the impact of rainfall spatial resolution was insignificant for catchment sizes above 250 km 2 and negligible for catchments larger than 1000 km 2 . A recent study, [15] demonstrated that, the impact of spatial resolution on flow simulation was scale, catchment and event characteristic-dependent.…”
Section: Effects Of Spatial Resolutionsupporting
confidence: 91%
“…These authors used rainfall datasets at spatial resolutions of 0.05 • , 0.1 • , 0.25 • and 0.5 • . Results from this study also corroborate the findings of Fu et al [37], where the authors demonstrated that, the impact of rainfall spatial resolution was insignificant for catchment sizes above 250 km 2 and negligible for catchments larger than 1000 km 2 . A recent study, [15] demonstrated that, the impact of spatial resolution on flow simulation was scale, catchment and event characteristic-dependent.…”
Section: Effects Of Spatial Resolutionsupporting
confidence: 91%
“…In their study, the distributed data outperformed lumped data in the simulation results. A similar study was conducted by Fu et al (2011), who used the MIKE SHE model (Abbott et al, 1986). However, in this case a clear effect of rainfall distribution was visible only on groundwater head and recharge.…”
Section: Introductionmentioning
confidence: 93%
“…Relic Saale moraine hills are predominately found in the northwest and west of the catchment. The land use consists of 60.5 % agriculture, 17.4 % grass, 14.0 % forest, 6.3 % heath, and 1.8 % urban areas (Fu et al, 2011).…”
Section: Study Area and Datamentioning
confidence: 99%